Tunisia's Global Integration : A Second Generation of Reforms to Boost Growth and Employment - World Bank (Washington, DC : World Bank, 2012)
This study on a world integration for Tunisia attempts to contribute to the achievement of the growth of the 11th development plan. It first takes stock of past integration policies, outlining policies implemented and assessing their impact on foreign direct investments (FDI), exports and employment. Then, it examines the current challenges of integration of Tunisia, which is both global and multisectoral pursuant to the actual creation of a free trade area with Europe for industrial products in January 2008. In the light of challenges expected, another generation of integration reform is identified to further improve the positioning of a competitive Tunisia and realize the potential growth in services. The report contains four chapters. Chapter one analyzes integration policies implemented since the early 70s and evaluates the impact thereof on the FDI, exports and employment. Chapter two examines the current challenges and major reforms necessary to correct the side-effects of past integration policies. Chapter three attempts to identify the reforms necessary to improve quality and lower prices of services. Finally, chapter four examines the prospects for export of professional services (accounting, auditing, legal services) and health by Tunisia, which showed a real capacity to compete in these areas in recent years.